EXPLORING PERCEPTION OF POST GRADUATE STUDENTS TOWARDS VIDEO BASE LEARNING - Anita Maharani; Dewi Tamara (Jurnal Muara Pendidikan, 2021)
This study aimed to find out the views of students at the undergraduate level about learning using video-based learning. The method used in this research is classroom action research, and this research was conducted in the Master of Management program, Bina Nusantara University, located in Jakarta. This research was done between the 2019 – 2020 academic year and the Covid-19 pandemic between February 2020 and June 2020. The subjects within the study were first-year students in the second-level program, and of the 25 people in the class, three volunteers participated in this research. The results of this study indicate that the possibility of successful video-based learning and the results obtained have the opportunity to have a positive impact on learning at the second-level level, only with a note that input from participants needs to be considered, including those related to the duration and appearance of video-based learning.